UPAYA GURU PENDIDIKAN AGAMA ISLAM DALAM MENINGKATKAN HASIL PRESTASI BELAJAR SISWA MELALUI IBADAH MAHDHAH DI SDN KARANGBANYU 4 TAHUN AJARAN 2022/2023 - Nurhasanah, Muwahidah; Aryanti, Puspitasari (Jurnal Al-Ilmu: Jurnal Penelitian dan Pendidikan Madrasah Ibtidaiyah, 2023)
Worship is one of the many mistakes made by humans. The apostles and books must be sent down to realize this goal. People who truly believe in Allah Ta'ala will certainly compete in worshiping Allah Ta'ala. However, because the practice focuses on worship itself, such as prayer, zakat, or fasting, one's focus shifts to worship itself. Mahdhah worship is worship ordered by Allah SWT. This worship has a pure nature. That is, the provisions cannot be changed and must follow what has been determined by Allah SWT. The efforts of Islamic religious education teachers at SDN Karangbanyu 4 Widodaren Ngawi have become a measure of success in increasing student achievement results. Religious activities in mahdhah worship such as prayer, fasting and zakat. Efforts made by teachers of Islamic religious education aim to improve student worship and learning achievement. This study aims to determine the results of the application of Islamic religious education teachers in improving student learning outcomes through mahdhah worship. This research uses a qualitative type with observation techniques, interviews and documentation. This research was conducted at SDN Karangbanyu 4, Widodaren, Ngawi. The results of this study indicate that with the efforts of Islamic religious education teachers through mahdhah worship, student achievement results increase and are more effective in understanding mahdhah worship such as prayer, fasting, zakat. It is hoped that future researchers will discuss the effectiveness of implementing ghairu mahdhah worship.